Examining pycho-social wellbeing among factory workers - Kumar, Shankar; Reddy, Nellore Pratika (Intelektual Pustaka Media Utama, 2025)
In India, factory employees make up a sizeable portion of the labor force and are essential to the country's industrial sector. Working in a factory may be mentally and physically demanding, which can lead to stress, burnout, and other mental health issues. The researcher in the study focused on the impact of mental wellbeing on job performance and examining the mediating effect of job satisfaction and moderating effect of social competence among factory workers. The study's target population is factory workers working in the locality of Tamil Nadu with a sample size of 114 workers. A descriptive study design with a quantitative approach and non-probability convenience sampling is applied. The hypotheses formulated were tested by using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS. It is evident from the study there is a significant impact on mental wellbeing on job performance; mental wellbeing on job satisfaction and job satisfaction on job performance. Prioritizing mental health in the workplace shows a dedication to the all-encompassing care of employees and promotes a positive organizational culture that values employee wellbeing. These factors will positively affect employee health and happiness, productivity, absenteeism rates, turnover rates, workplace safety, and ethical responsibility. Future studies can concentrate on mindfulness training, stress management initiatives, and counseling services on performance results.